2023
DOI: 10.5755/j01.ee.34.1.32159
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Investment, Eco-Innovation, and Financial Inclusion on Sustainable Development: Evidence from China

Abstract: Recently, sustainable development is demanded to be a compulsory requirement by international communities due to environmental and economic instability, hence, encouraging scholars to explore various approaches through which countries could achieve it. In this lieu, the present article explores the concept of green investment, eco-innovation, and financial inclusion and their effectiveness on sustainable development in the context of China. The article has extracted the data from secondary sources like Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…Internal and external resources can influence green innovation through capacity development and capital investment. According to resource orchestration theory, an organization can only derive maximum benefit from its resources and capabilities when they are structured, combined, and managed effectively (Chen et al 2023 ; Chien 2023 ; Chien et al 2023a ). Therefore, with abundant green knowledge capital, businesses can implement green innovation conveniently and effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal and external resources can influence green innovation through capacity development and capital investment. According to resource orchestration theory, an organization can only derive maximum benefit from its resources and capabilities when they are structured, combined, and managed effectively (Chen et al 2023 ; Chien 2023 ; Chien et al 2023a ). Therefore, with abundant green knowledge capital, businesses can implement green innovation conveniently and effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with these findings, a study conducted on a sample of over 55,000 firms in 79 countries found that financial inclusion has a positive impact on firms’ growth and can contribute to higher levels of economic development (Chauvet and Jacolin, 2017). Similarly, a recent research documents positive and significant relationship between financial inclusion factors, such as the number of commercial bank branches, depositors and borrowers, and sustainable development, as measured by the Human Development Index in China (Chien, 2023). Other studies have been conducted to investigate the relationship between financial inclusion and economic development in various countries such as Iraq, Nigeria and Kenya.…”
Section: Resultsmentioning
confidence: 94%
“…The ability of businesses to respond to environmental restrictions through green innovation has been identified as a critical component in determining the environmental and economic performance of organizations and communities (Liao et al, 2023). Numerous studies have been conducted to determine the value of green innovation; the most critical factors were found to be raising the standard of living, increasing R&D spending, boosting profits, fostering a culture of environmental responsibility, boosting organizational output, implementing proactive environmental strategies to react to environmental challenges, and advancing technological advancements (Chien, 2023;Udeagha & Ngepah, 2023).…”
Section: Green Innovation Technology and Sustainable Successmentioning
confidence: 99%